PELIMPAHAN PORSI CALON HAJI YANG TELAH WAFAT KEPADA SALAH SATU AHLI WARIS MENURUT PERSPEKTIF HUKUM WARIS ISLAM - moulia, nouvan; Muharrir, Muharrir; Fazzan, Fazzan (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2024)
The performance of the Hajj pilgrimage is one of the pillars of Islam that must be fulfilled by Muslims who possess the ability (istita'ah). Due to the overwhelming number of applicants and the restrictions on the number of pilgrims allowed to depart each year imposed by the Saudi Arabian government, the Ministry of Religious Affairs of the Republic of Indonesia has limited the departure of prospective Hajj pilgrims through a quota system and the allocation of waiting numbers known as "nomor porsi" (quota numbers). This quota and waiting list system has resulted in a waiting period for prospective Hajj pilgrims in Indonesia reaching up to 46 (forty-six) years from the time of registration. One consequence of this situation is that some prospective Hajj pilgrims who have registered and received their quota numbers may pass away before their departure. To address this issue, the Director General of Hajj and Umrah Implementation has issued Decree Number 130 of 2020, which allows for the transfer of quota numbers to one of the heirs of a deceased prospective Hajj pilgrim who did not have the opportunity to perform the pilgrimage. The transfer of the Hajj quota to one of the heirs has sparked debate in society regarding its status: whether the quota is part of the inheritance that must be divided among the heirs or whether it is not considered part of the inheritance. The research method employed is normative juridical with a conceptual approach. The findings of the study indicate that the Hajj quota of a deceased prospective pilgrim is part of their rights that fall into the category of inheritance. When such a right falls into this category, it can become an inheritance that must be divided among heirs who meet the requirements.